Quality Changes Of Kappaphycus alvarezii Jelly Candy Coated With Gelatin-Chitosan-Nanochitin Composites-Edible Film During Storage - Sri Rahayu Cahyani; Asri Silvana Naiu; Nikmawatisusanti Yusuf (Universitas Negeri Gorontalo, 2023)
This study aims to analyze changes in the quality of Kappaphycusalvarezii seaweed jelly candy packaged in edible film based on chitosan-nano chitin gelatin composite during storage. The research method used was a laboratory experimental method. The research stage consisted of preliminary research aimed at determining the formula for edible film gelatin-chitosan enriched with nanochitin. The main research was applying the best formulation of edible film gelatin- chitosan-nanochitin to seaweed jelly candy which was then stored for 60 days that was converted to 15 days in a climatic chamber at 40 °C and 75% humidity. The chemical characteristics tested were water content and reducing sugar content, microbiological tests including TPC and molds-yeasts and sensory characteristics were tested every 3 days. The design of data analysis used linear regression. The results of the preliminary study showed that the best edible film formula was composed of 2% gelatin, 2% chitosan and 0.2% nanochitin, which resulted in a water vapor transmission rate of 15.25 g/m2/day and has an attractive appearance. Based on the standard SNI (2008), the moisture content of jelly candy packaged in edible film gelatin-chitosan-nanochitin can be maintained until the 36th day of storage, which is 19.25%, the reducing sugar content up to the 60th day of storage is 20.5%, TPC up to 20.5%. the 60th day of storage is log 3.5 CFU/g, and the sensory quality can be maintained until the 36th day. The molds and yeasts were not visible during storage.